2020
DOI: 10.4209/aaqr.2020.05.0190
|View full text |Cite
|
Sign up to set email alerts
|

Study on Influencing Factors and Control Strategies of Surgical Smoke Concentration Distribution

Abstract: Paroxysmal fumes during surgical operations endanger the health of medical staff. Special measures for removing surgical smoke are lacking. Article Real-time monitoring of particulate matter concentrations in surgical smoke at different locations under different surgical conditions were explored, and a particulate matter purification control strategy was proposed. The PM2.5 and PM10 concentrations in the operating and respiratory zones near the operating table were about 3.0 times more than the specified value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The data measured by the TSI 3330 optical particle size analyser showed that more than 70% of the smoke particles had a particle size of approximately 0.3 microns, as shown in Figure 4. Notably, electrosurgical instruments can produce particles as small as 0.3 microns [3,4,40]. Therefore, the particle size in the simulation was set to 0.3 microns.…”
Section: Particle Phase Simulationmentioning
confidence: 99%
“…The data measured by the TSI 3330 optical particle size analyser showed that more than 70% of the smoke particles had a particle size of approximately 0.3 microns, as shown in Figure 4. Notably, electrosurgical instruments can produce particles as small as 0.3 microns [3,4,40]. Therefore, the particle size in the simulation was set to 0.3 microns.…”
Section: Particle Phase Simulationmentioning
confidence: 99%